FARMERS’ ATTITUDES TOWARDS VETERINARY DRUGS USE AND AWARENESS OF ANTIBIOTIC RESIDUES IN DAIRY ENTERPRISES IN TURKEY - Petek Piner Benli; Pinar Ayvazoglu Demir (Journal of Animal and Plant Sciences, 2023)
Veterinary drugs residues in food derived from animals have a direct impact on human and animal health as well as the food industry. The study aims to evaluate farmers' attitudes toward veterinary drugs use and awareness of antibiotic residues in three provinces and central villages where conventional dairy cattle farms are widely distributed in southern Turkey, using the survey technique. The farmers were surveyed in September to October 2021. The results showed that a significant number of the farmers surveyed in the current study had positive attitudes towards use of veterinary drugs including consultation with a veterinarian, using prescribed veterinary drug, following the instructions in the prescription, reading the prospectus, paying attention the expiration date and the suitability of a drug for a specific disease. In addition, the findings demonstrated that a significant part of the farmers had a higher awareness about the antibiotic residues including use, duration, storage, withdrawal periods of antibiotics and resistance of microorganisms. As a result, the farmers had positive attitudes towards use of veterinary drugs and a higher awareness related to the antibiotic residues in southern Turkey.
Keywords: attitudes; awareness; drug use; antibiotic residues; farmers; dairy enterprises